0.18(y-1)+0.10y=0.04y-1.2

Simple and best practice solution for 0.18(y-1)+0.10y=0.04y-1.2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 0.18(y-1)+0.10y=0.04y-1.2 equation:


Simplifying
0.18(y + -1) + 0.10y = 0.04y + -1.2

Reorder the terms:
0.18(-1 + y) + 0.10y = 0.04y + -1.2
(-1 * 0.18 + y * 0.18) + 0.10y = 0.04y + -1.2
(-0.18 + 0.18y) + 0.10y = 0.04y + -1.2

Combine like terms: 0.18y + 0.10y = 0.28y
-0.18 + 0.28y = 0.04y + -1.2

Reorder the terms:
-0.18 + 0.28y = -1.2 + 0.04y

Solving
-0.18 + 0.28y = -1.2 + 0.04y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-0.04y' to each side of the equation.
-0.18 + 0.28y + -0.04y = -1.2 + 0.04y + -0.04y

Combine like terms: 0.28y + -0.04y = 0.24y
-0.18 + 0.24y = -1.2 + 0.04y + -0.04y

Combine like terms: 0.04y + -0.04y = 0.00
-0.18 + 0.24y = -1.2 + 0.00
-0.18 + 0.24y = -1.2

Add '0.18' to each side of the equation.
-0.18 + 0.18 + 0.24y = -1.2 + 0.18

Combine like terms: -0.18 + 0.18 = 0.00
0.00 + 0.24y = -1.2 + 0.18
0.24y = -1.2 + 0.18

Combine like terms: -1.2 + 0.18 = -1.02
0.24y = -1.02

Divide each side by '0.24'.
y = -4.25

Simplifying
y = -4.25

See similar equations:

| 6+11z-2=9z+68-6z | | 25/28*4/51*17/50 | | 2(3x+6)=136 | | y/12+4=-7 | | -12-2+14=17 | | 9(x-2)+5=-13 | | (x+6)(x^3-3x+5)= | | 2x=16/9 | | x^2+y^2-6/5x+9/25-9=0 | | 6a+12=2a+-16 | | -4(7)+2(-9)-7(-9)=z | | 3*4/5 | | (x-4)(x^2-7x+2)= | | m+3m+4m+4= | | 2/6*3/4 | | 44-5h=6h | | X=20+-0.4y+-0.02z | | 9x-3(x-8)=6(x-3)+6 | | 20000(.06x+.07y)=1300 | | 9x-3(x-8)=6x-24 | | 13q-2=-28 | | 6-2x=4(2-3x)+8x | | 9=-2m+-1 | | .93x+.97(4-x)=3.8 | | 2(x-4)-x=3 | | (3x-3)(3x-8)= | | 1+8(-4n-2)=-39-8n | | -2/3r+2r=6/5r+12/5 | | (4x^2+1)(6x^2+7)= | | 5x-6-2x=4x+8 | | 6x+6=6x-9 | | 2/3(6x+9)=18 |

Equations solver categories